PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMAN 3 PADANG - Juwita, Mutiara (Jurnal Edukasi dan Penelitian Matematika, 2024)
An important skill that must be developed by students in learning mathematics is the ability to solve mathematical problems well. The results of the observation study at SMAN 3 Padang show that this competency is still lacking. This study looks at how well Discovery Learning can work for this particular skill. Class XI of SMAN 3 Padang was the main research population. Class XI F.1 and class XI F.10 served as the sample groups, which were selected by simple randomization. This study used a non-equivalent posttest only design. The results showed that the alternative hypothesis (H0) was accepted if the P-value < significance level. The results of the empirical study indicate that the Disovery Learning model improves problem solving ability. Keywords–Discovery Learning, Problem Solving, Direct Instrucstion